1994
DOI: 10.1002/micr.1920150512
|View full text |Cite
|
Sign up to set email alerts
|

Phalloplasty for female transsexuals with sensate free forearm flap

Abstract: One of the primary goals of phalloplasty on female to male transsexuals is to void while standing. However, achieving competence of the neourethra, sensation, and rigidity of the neophallus still present a challenge. Over a 5 year period (1988-1993), 56 phalloplasties using sensate free forearm flaps were performed for 56 primary female transsexuals. The urethrocutaneous fistula rate was 38/56 and one flap totally necrosed. However, when the flap was prefabricated with a tubed graft of vaginal mucosa for the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 15 publications
0
67
0
4
Order By: Relevance
“…30 catheter may be inserted in a subcutaneous tunnel extending from one meatal incision to the other. 10 Both these incisions are made in a triangular fashion, and the resulting triangular skin flaps are folded inward into the subcutaneous tunnel to prevent stenosis of the otherwise circular meatal scar (Fig. 1).…”
Section: Urethroplastymentioning
confidence: 99%
“…30 catheter may be inserted in a subcutaneous tunnel extending from one meatal incision to the other. 10 Both these incisions are made in a triangular fashion, and the resulting triangular skin flaps are folded inward into the subcutaneous tunnel to prevent stenosis of the otherwise circular meatal scar (Fig. 1).…”
Section: Urethroplastymentioning
confidence: 99%
“…Fistula formation is the most frequent complication, with reported incidence ranging from 40 to 100 percent. [1][2][3][4] Urethral stenoses are less frequent than urethrocutaneous fistulae, but represent a difficult problem. Biemer 4 reported on 14 transsexual patients with an incidence of strictures of 29 percent.…”
Section: Discussionmentioning
confidence: 99%
“…Flap success rates over 90 percent have been reported in a recent series. 1 Urethrocutaneous fistula is reported as the most common postoperative complication, with an incidence of 68 percent in the early series of Fang et al 2 Urethral stricture is less frequently reported, usually occurring at the junction of the native urethra and the neourethra. It is usually due to technical mistakes or vascular complications, and its treatment is difficult.…”
mentioning
confidence: 98%
“…The complication rate is relatively high, especially for urethral stenosis and formation of fistula [12]. Moreover, there is always a large scar in the donor area, with possible functional loss [13].…”
Section: Comparison With Other Methodsmentioning
confidence: 99%